The Effect of management trainee programs on employee commitment - Kinyua, Emma Kendi (Strathmore University, 2014)
This study investigated the effect of management trainee programs on employee commitment, specifically looking at the effect of (a) the selection criteria of the trainees, (b) the management trainee program content, (c) the management trainee program delivery and (d) the trainee socialization on employee commitment. Previous studies have established that talent management and employee commitment are critical issues in today's business world, and management trainee programs are one of the tools of talent management. The study therefore sought to investigate the effect of management trainee programs on three types of commitment that were advanced in the 1980s; affective, continuance and nonnative commitment. This study was conducted on graduates of the management trainee programs in companies in Kenya, and specifically targeted those companies with offices in Nairobi as these were considered representative of the companies that have management trainee programs. The study used self-administered questionnaires sent to the graduates of the programs mostly via their human resources managers who needed to vet the questionnaires. The data collected was coded and analyzed using Statistical Package for Social Studies (SPSS) software and results reported fully. The data was summarized using frequency tables and analyzed using descriptive analysis and regression analysis. Confidentiality was maintained throughout the study, during the data collection and even during analysis of the same. The results of the study revealed that of the four variables that were being assessed, the management trainees liked the program content the most and the program delivery the least. The study concluded that the commitment type that was most affected by the management trainee programs was affective commitment, followed by normative commitment and lastly continuance commitment. As a result of the findings, organizations seeking to promote employee commitment would be encouraged to set up management trainee programs and pay attention especially to the course content as this is the variable that had the greatest impact on the affective commitment and also ensure that they do not delay the appointment of trainees into their first management position since this was seen to have a negative correlation to the commitment levels.
Submitted in partial fulfillment of the requirements for the Degree of Master of Business Administration at the Strathmore Business School